ChemInform Abstract: Enhanced Photocatalytic Activity of S‐Doped BiVO4 Photocatalysts. Issue 39 (September 2015) - Guo, Minna; Wang, Yang; He, Qianglong; Wang, Wenjie; Wang, Weimin; Fu, Zhengyi; Wang, Hao
Abstract BiVO4:Sx (x = 0, 0.1, 0.3, 0.5, 0.7, 0.9) photocatalysts are prepared by surfactant‐free hydrothermal treatment of an aq.